Genomic characterization of carbapenem and colistin-resistant Klebsiella pneumoniae isolates from humans and dogs - Pachanon, Ruttana; Khine, Nwai Oo; Phumthanakorn, Nathita; Wongsurawat, Thidathip; Niyomtham, Waree; Chatsuwan, Tanittha; Hampson, David J.; Prapasarakul, Nuvee (Frontiers in Veterinary Science, 2024)
Carbapenem and colistin-resistant Enterobacteriaceae, including Klebsiella pneumoniae, have become a growing global concern, posing a significant threat to public health. Currently, there is limited information about the genetic background of carbapenem and colistin-resistant K. pneumoniae isolates infecting humans and dogs in Thailand. This study aimed to characterize carbapenem and colistin-resistant genes in six resistant K. pneumoniae clinical isolates (three from humans and three from dogs) which differed in their pulse field gel electrophoresis profiles. Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), antimicrobial susceptibility testing, and whole-genome sequencing were employed to identify and analyze the isolates. All six isolates were carbapenemase-producing K. pneumoniae isolates with chromosomally carried blaSHV, fosA, oqxA and oqxB genes, as well as nine to 21 virulence genes. The isolates belonged to five multilocus sequence types (STs): one isolate from a human and one from a dog belonged to ST16, with the other two human isolates being from ST340 and ST1269 and the other two dog isolates were ST147 and ST15. One human isolate and two dog isolates harbored the same blaOXA-232 gene on the ColKP3 plasmid, and one dog isolate carried the blaOXA-48 gene on the IncFII plasmid. Notably, one human isolate exhibited resistance to colistin mediated by the mcr-3.5 gene carried on the IncFII plasmid, which co-existed with resistance determinants to other antibiotics, including aminoglycosides and quinolones. In conclusion, this study provides a comprehensive characterization of both chromosome- and plasmid-mediated carbapenem and colistin resistance in a set of K. pneumoniae clinical isolates from unrelated humans and dogs in Thailand. The similarities and differences found contribute to our understanding of the potential widescale dissemination of these important resistance genes among clinical isolates from humans and animals, which in turn may contribute to outbreaks of emerging resistant clones in hospital settings.